2021
DOI: 10.3389/fonc.2021.715552
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals the Migration of Osteoclasts in Giant Cell Tumor of Bone

Abstract: Giant cell tumor of bone (GCTB) is benign tumor that can cause significant osteolysis and bone destruction at the epiphysis of long bones. Osteoclasts are thought to be highly associated with osteolysis in GCTB. However, the migration of osteoclasts in GCTB remains unclear. A deeper understanding of the complex tumor microenvironment is required in order to delineate the migration of osteoclasts in GCTB. In this study, samples were isolated from one patient diagnosed with GCTB. Single-cell RNA sequencing (scRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…We have previously shown that EGFL7 is expressed in GCTB tumor tissues. 1 Additional studies detected and localized expression of EGFL7 in OS tissues. 31 VEGF - A was identified in both OS and GCTB tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that EGFL7 is expressed in GCTB tumor tissues. 1 Additional studies detected and localized expression of EGFL7 in OS tissues. 31 VEGF - A was identified in both OS and GCTB tissues.…”
Section: Resultsmentioning
confidence: 99%
“…To define the heterogeneity of GCTB and OS tumor cells at the transcriptional level, we performed bioinformatic analysis using results obtained from our previously published studies. 1,30 The mRNA expression data used in this study were downloaded from the NCBI Gene Expression Omnibus database. We refer to each dataset by the first author’s last name and cancer type.…”
Section: Methodsmentioning
confidence: 99%
“…CCNA2 also has important roles in initiating osteogenesis, adipogenesis, and chondrogenesis (34). In particular, CD137 not only has a high degree score in the PPI network but also are closely related to osteoclasts based on Feng's study (35). CD137L and CD137 expressed on BMSCs promote the osteogenic differentiation through p53 Wnt/b-catenin signaling.What is more, we speculated that CD137 expression was up-regulated in BMSCs isolated of aged mice, affecting the osteogenic differentiation of BMSCs by the p53 Wnt/b-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Third, while the giant cells in TGCT and GCTB appear quite large in histologic images, the giant cells in GCTB have been measured as having size range of 10-300um (31). Finally, other groups were also able to study giant cells using single cell sequencing, such as the single cell study of GCTB (32, 33). The presence of giant cells in the scRNA data allowed to compare them to those found in Giant Cell Tumor of Bone (GCTB) that has several similarities with TGCT.…”
Section: Discussionmentioning
confidence: 99%